Pendekatan Art Therapy untuk Perilaku Interaksi Sosial Bagi Penyandang Autism di Art Therapy Center Widyatama, Bandung, Jawa Barat. - Firzayafi Hidajat Putra; Irhamni Rahman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Autism Spectrum Disorder (ASD) is often associated with challenges in aspects of social interaction and communication. Art Therapy, which utilizes the creative process in art as a therapeutic medium, is believed to help improve social and emotional skills in individuals with ASD. This research aims to explore the effectiveness of the Art Therapy approach in improving social interaction behavior in individuals with autism at the Art Therapy Center Widyatama Bandung. This study uses qualitative methods with a descriptive approach to assess the impact of Art Therapy on participants' social behavior. Data was collected through direct observation, interviews with therapists, alumni and parents. The results of the study show that Art Therapy can contribute significantly to changing the social interaction behavior of people with autism, with visible behavioral changes in self-expression, non-verbal communication, and skills.